A Holistic Perspective on Nasal Polyps (Homoeopathy for All, 2024)
Nasal polyps are non cancerous,  painless growths in the lining of nasal  passages or sinuses. They appear as  a result of chronic inflammations  generally associated with asthma,  allergic rhinitis, chronic sinusitis.  Despite being benign, nasal polyps  may cause significant discomfort,  disruption of normal nasal function,  nasal congestion, loss of smell and  sinus infections.
Keywords: Diagnosis; Definition; Management